2017
DOI: 10.1002/oby.22012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methods for Analyzing Human Adipose Tissue Macrophage Content

Abstract: Objective The relationship between inflammation, obesity and adverse metabolic conditions is associated with adipose tissue macrophages (ATM). We compared the measurements of human ATM using flow cytometry, immunohistochemistry (IHC) and RT-PCR of ATM markers. Methods We evaluated a new software program (AMCounter) to help measure ATM using IHC and compared this to flow cytometry and RT-PCR. Results IHC had good intra-individual reproducibility for total (CD68), pro-inflammatory (CD14) and anti-inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…For the purpose of the current study we included the entire spectrum of vegetarian diets. We chose to study obese omnivores and BMI-matched vegetarians (one vegetarian had a BMI of 28 kg/m 2 ) because our database (derived from our methodology studies [16]) indicate that substantial increases in ATMs occur primarily with BMI’s above 30 kg/m 2 . It would be more difficult to detect a difference between omnivores and vegetarians if the omnivores already have a low ATM burden.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the purpose of the current study we included the entire spectrum of vegetarian diets. We chose to study obese omnivores and BMI-matched vegetarians (one vegetarian had a BMI of 28 kg/m 2 ) because our database (derived from our methodology studies [16]) indicate that substantial increases in ATMs occur primarily with BMI’s above 30 kg/m 2 . It would be more difficult to detect a difference between omnivores and vegetarians if the omnivores already have a low ATM burden.…”
Section: Discussionmentioning
confidence: 99%
“…For immunohistochemistry (IHC), adipose tissue samples (~ 350-400 mg) were processed and the staining procedure was performed as previously described [16]. The adipose tissue sections were visualized by light microscopy using an Olympus BX43 microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each method has benefits and drawbacks, which are summarised in Table 1 . For example, it has been shown that immunohistochemistry yields reproducible results, but with flow cytometry, the recovery of macrophages after tissue digestion can be a possible source of variation ( 50 ). However, there is good agreement between flow cytometric analysis of adipose tissue cellular composition and the expression mRNA for key cell surface markers across a range of adiposities in humans (Figure 1 ) ( 35 ).…”
Section: Methodological Considerations In Adipose Tissue Immunologicamentioning
confidence: 99%
“…Although studies in mice fed HFD overwhelmingly described the ATM accumulation in the VAT of obese animals, 1,2,4,5,8,17 human data are scarcer and more inconsistent. 10,[31][32][33][34] These discrepancies may be explained by the use of different experimental protocols 35 and by the heterogeneity of the human populations evaluated. After dissecting the ATM subsets present in the obese VAT, we find that the net ATM count was the consequence of CLEC5A + ATM loss together with the increment in the numbers of a CD11c + CLEC5A À ATM subset.…”
Section: Discussionmentioning
confidence: 99%